NOX4 inhibition protects enteric glial cells against Clostridium difficile toxin B toxicity via attenuating oxidative and Endoplasmic reticulum stresses. (3rd August 2019) - Jiang, Yanmin; Xu, Lan; Yu, Lin; Xu, Xiang; Feng, Chen; Li, Jianbo
Abstract: Enteric glial cells (EGCs), one main cell population of the enteric nervous system (ENS), play a major role in regulating intestinal barrier function. Clostridium difficile toxin B (TcdB) is the major virulence factor produced by C. difficile and estimated to be toxic to EGCs by inducing cell death, cell cycle arrest, and inflammatory cytokine production; however, the detailed mechanism for such effect is still unclear. In this study, we further evaluated the toxic effect of TcdB on EGCs and the involvement of NADPH oxidases in such process using the rat-transformed EGCs (CRL-2690). The results showed that NOX4 was activated by TcdB in EGCs and functioned as the major factor causing cytotoxicity and cell apoptosis. Mechanically, NOX4-generated H2 O2 was the inducer of oxidative stress, Ca 2+ homeostasis disorder, and ER stress in EGCs upon TcdB treatment, and NOX4 inhibition protected EGCs against TcdB toxicity via attenuating these dysfunctions. These findings contribute to our understanding of the mechanism by which TcdB affects EGCs and suggest the potential value of NOX4 inhibition for treatment against C. difficile infection.